Microstructure‐Based Modeling of Mechanical Properties and Deformation Behavior of DP600 Dual Phase Steel. Issue 12 (17th September 2019) - Li, Shengci; Guo, Chengyu; Hao, Leilei; Kang, Yonglin; An, Yuguo
Abstract : Herein, the modeling approach for predicting the work hardening flow curve of DP600 steels from the real microstructure and comparison between micromechanical modeling and experimental shear loading are described. A real microstructure‐based model by representative volume element (RVE) method is used to evaluate the microstructure deformation. The flow behavior of ferrite and martensite single phase is predicted by a dislocation‐based model. Results show that the work hardening predicted by the simulation under shear loading condition is consistent with the experimental data. An increased carbon in ferrite phase can increase the strength and strain hardening rate of a given steel. Simulation indicates that the strain is mainly concentrated in the ferrite, and the plastic strain localization is mainly located at the ferrite grains along the phase boundaries; martensite carries most of the stress. The distribution and morphology of martensite affect the deformation behavior of dual phase (DP) steel. A predominant shear failure mode is developed and instability occurs under uniaxial loading. Abstract : A real microstructure‐based model by representative volume element method is used to evaluate the deformation behavior of DP600 steel. The results predicted under shear loading condition are consistent with the experimental data; a predominant shear failure mode is developed and instability occurs under uniaxial loading. The distribution and morphology of martensite affect the deformation behavior of dual phase steel.